Differentiation of Arabica Coffee from Several Regions and Roasting Condition by Detecting Released Gases using Electronic Food Nose - Belgis, Maria; Witono, Yuli; Vico Danuartha, Laurensius Ardian; Taruna, Iwan; Suryadharma, Bertung (Indonesian Coffee and Cocoa Research Institute, 2025)
This study was aimed to identify the differentiation of Arabica coffee from West Java, East Java, West Nusa Tenggara and Bali using an electronic food nose. The analysis was conducted based on variations in temperature and roasting time to evaluate the effect of these parameters on coffee aroma characteristics. This research used an electronic nose device to detect volatile compounds quickly and accurately. The electronic nose was equipped with MQ-3, MQ-8, MQ-135, and MQ-136 sensors, able to detect alcohol, hexane, hydrogen, carbon dioxide, and hydrogen sulfide gas. Arabica coffee from various parts of Indonesia was roasted on three levels (light, medium, and dark). The results showed that variations in roasting temperature (220, 230, and 240 Â°C) and time (10, 13, and 17 min) significantly affected the volatile compoundsâ€™ profile. The temperature and roasting time correlated proportionally to the hexane gas, CO2 , and alcohol produced. Conversely, the lower the temperature and the faster the roasting process, the higher H2S gas was produced. Based on this, using an electronic nose effectively distinguishes the aroma characteristics of coffee based on differences in temperature and roasting time. This research contributes to helping improve the quality of Indonesian arabica coffee by understanding how temperature variation and roasting time length can be used to optimize the coffee production process and improve the coffee quality produced.